Strategy for Accelerating Development of the National Sharia Economic and Financial Committee (KNEKS) Efforts to Improve Sharia Financial Institutions in Indonesia - Efendi Sugianto (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2024)
Sharia economic and financial development is directed as one of the pillars to strengthen national economic resilience to improve community welfare, in encouraging Sharia economic and financial development adhering to the vision of Sharia economic and financial development which places it as a rational choice for society, namely providing benefits and value In addition, in carrying out economic activities better, sharia economic activities and financial products can become a lifestyle for everyone, so that sharia economics and finance are not exclusive things, but make them inclusive and universal by the principles of rahmatan lil alamin. This research uses a qualitative approach because the type of data used leads to qualitative data with an emphasis on in-depth issues, including the important role of the National Sharia Financial Economics committee, the data sources needed and obtained by the author directly from observations of transactions in using online facilities. as well as documents from the internet. Other data sources relate to literature and library materials, both from books and journal articles related to Islamic financial economics. In the context of Sharia finance, encouraging the Indonesian Sharia finance industry to become a global player with an international reputation and credibility. KNEKS is one of the breakthrough steps to increase the effectiveness and efficiency of implementing national development plans in the Sharia finance and economic sector. Through KNEKS programs it is hoped that goals can be achieved that will produce real results for the general public and the world community.